Lietuvių DP knyginiai ryšiai su latvių ir estų DP Vakarų Europoje 194S-19S2 metais - Misiūnas, Remigijus (Knygotyra, 1999)
Thousands of Lithuanians, Latvians, and Estonians left their native lands during World War II. They escaped from the second Soviet occupation and spent the post-war years in displaced persons (DP) camps in various West European countries. The living conditions in the camps were very difficult, but the social and cultural activity of the DPs was vibrant. Book publishing was one expression of this activity. Since DPs from the Baltic States lived in the same camps, they had book connections. Several areas of their activity can be discussed.One of these was the publishing activity of Baltic DP joint institutions such as the Baltic University, the Lithuanian-Latvian Unity, the Baltic Society of Philately "Baltia," and others. A few books were published as a result of joint Baltic efforts, such as art exhibitions, poetry competitions, or individual initiatives (e.g., Salomėja Narkėliūnaitė, Aleks Rannit, V. K. Jonynas, and others).Many publishing ideas were not realized (e.g., a book about the Meerback Baltic DP camp, the Vorarlberg DP camp Baltic almanac "Lootus-Ceritas-Viltis," a collection of Baltic writers' prose in German, a map of the three Baltic states, and others). Some Latvian and Estonian DP books caused dissatisfaction among Lithuanian DPs as they allocated Vilnius and the Vilnius area to Poland.The book connections between Lithuanian DPs and Latvian and Estonian DPs were sporadic, but this tradition continued after 1952 in various countries where Baltic emigrants lived.